AB1386 Rheumatologists play a key role in shared decision-making with patients in the choice to initiate biologic therapy for treatment of rheumatoid arthritis. (23rd January 2014) - Bolge, S.; Schenkel, B.; Lorenzo, R.; Ramesh, V.; Ingham, M.P.
Abstract : Background: There has been increasing focus on the importance of patients participating in the treatment decision-making process with their physicians. Previous research has demonstrated that effective physician-patient communication, a key component of shared decision-making, has a positive impact on patient satisfaction and adherence to therapy. Objectives: This study describes the patient perspective on the shared decision-making process between patients and physicians when initiating biologic therapy for the treatment of rheumatoid arthritis (RA). Methods: Patients self-reporting a diagnosis of RA completed a self-administered, internet-based questionnaire in the Fall of 2011. A subset of patients currently using a biologic therapy to treat their RA provided details about the decision-making process for initiating their current biologic therapy. Results: A total of 2138 respondents (76% female, mean age 56.4) completed the questionnaire. Of these, 20% (n=434) were being treated with biologic therapy at the time of the study. Discussions about biologic therapy were most often initiated by a rheumatologist (91%); only a small proportion of patients reported that a primary care physician (4%), the patient themselves (3%), or another (2%) initiated the discussion. During the discussions, physicians most often focused on administration (77%), dosing schedule (77%), side effects (71%), safety risks (64%), importance of long-term use (57%), and importance of concomitant methotrexate use (53%). Patients rated the following as very or extremely influential (4 or 5 on a 5-point Likert scale) on the final decision to initiate biologic therapy: advice or recommendation by physician (76%), co-pay assistance to cover out-of-pocket costs (31%), advice or recommendation from other healthcare professional (28%), patient literature materials from physician office (27%), and information from general websites (22%). Most patients (71%) reported making the decision to start biologic therapy at the time of the initial discussion with their physician; mean time for all patients to make a decision to start biologic therapy was 12.2 days from the time of initial discussion. Conclusions: Rheumatologists are best positioned to ensure that patients have the necessary information to actively engage in the shared decision-making process for initiating biologic therapy. Rheumatologists most often initiate the discussion about biologic therapy, and patient decisions are most influenced by the advice or recommendation of their physician. Co-pay assistance programs are also influential in the patient decision to initiate biologic therapy and the rheumatology office may be well positioned to address this need. Future research should focus on potential outcomes benefits of shared decision-making. References: Elwyn G, et al. Shared decision-making in primary care: the neglected second half of the consultation. Br J Gen Pract 1999;49:477-82. Disclosure of Interest: S. Bolge Employee of: Janssen Scientific Affairs, LLC, B. Schenkel Employee of: Janssen Scientific Affairs, LLC, R. Lorenzo Consultant for: Janssen Scientific Affairs, LLC, V. Ramesh Consultant for: Janssen Scientific Affairs, LLC, M. ingham Employee of: Janssen Scientific Affairs, LLC